EVALUASI KESESUAIAN LAHAN UNTUK TANAMAN JAGUNG (Zea mays L.) BERDASARKAN SIFAT KIMIA TANAH DI KABUPATAEN PANGKEP - Nurfauziah, Nurfauziah; Nurmiaty, Nurmiaty; Kafrawi, Kafrawi (Agroplantae: Jurnal Ilmiah Terapan Budidaya dan Pengelolaan Tanaman Pertanian dan Perkebunan, 2025)
Evaluation of land suitability will provide information for land use in accordance with plant characteristics so that land can be used as it should. The purpose of this study was to determine the classification of land suitability for corn based on soil chemical properties in Pangkep Regency. This research was conducted from February to April 2024. Located in several districts in Pangkep Regency. This research was conducted using survey method. The technique used is by using Arc-GIS processing tools, digital land system data is cut with the administrative map of Pangkep Regency so as to obtain land system data for Pangkep Regency. Data on the chemical characteristics of Pangkep Regency were extracted from the land system data of Pangkep Regency to obtain data and maps of chemical characteristics of the Pangkep Regency area. Then the analysis of soil chemical characteristics for corn crop suitability matches the suitability of each soil chemical characteristic in Pangkep District with the requirements for growing corn crops based on the criteria of the Puslitbangtan Ministry of Agriculture. The conclusions that can be drawn from the study are 1.There is land with a land suitability class that is quite suitable (S2) ) for corn crops with a total area of 15,412 ha spread across several districts in Pangkep namely Kec. Balocci 3,275 ha, Bungoro 2,692 ha, Labakkang 116 ha, Mandalle 1,005 ha, Ma'rang 1,273 ha, Minasatene 338 ha, Segeri 1,334 ha and Todong Tallasa 5,378 ha. There is one sub-district where no suitable land was found, namely Pangkajene sub-district. 2.There is land with a land suitability class that is marginally suitable (S3) with a total area of 61,723 ha. Spread across several sub-districts in Pangkep district, namely Balocci sub-district 9,899 ha, Bungoro sub-district 6,207 ha, Labakkang sub-district 10,379 ha, Mandalle sub-district 3,519 ha, Ma'rang sub-district 8,212 ha, Minasatene sub-district 8,241 ha, Pangkajene sub-district 4,050 ha, Segeri sub-district 4,751 ha and Todong Tallasa sub-district 6,465 ha. 3.There is an unsuitable land suitability class (N) with a total area of 1,895 ha for corn crops in Pangkep District. Scattered in several kecematan in Pangkep district, namely Ma'rang sub-district 1 ha, Segeri sub-district 39 ha and Todong Tallasa sub-district 1,855 ha